Efficiency of Transcranial Direct Current Stimulation (tDCS) in Anorexia Nervosa Treatment - Case Report - Rząd, Zuzanna; Szewczyk, Paweł; Rog, Joanna; Karakuła-Juchnowicz, Hanna (Current Problems of Psychiatry, 2022)
Introduction. Transcranial direct current stimulation (tDCS) is a non-invasive brain stimulation with considerable potential as a treatment for many CNS disorders. Individuals suffering from eating disorders have elevated rates of lifetime depression, anxiety and obsessive-compulsive disorder, also affecting specific brain regions. More studies assess the effect of brain modulation in anorexia nervosa (AN). This study aimed to evaluate the effect, tolerability and safety of tDCS stimulation in the patient with an AN diagnosis.Material and method. The therapy was implemented in an 18-year-old female hospitalized at the I Department of Psychiatry, Psychotherapy and Early Intervention Medical University of Lublin. The simulation was performed twice daily for 25 minutes for two weeks, 20 sessions. To assess a. anthropometric measures, bioelectrical impedance analysis was conducted; b. biological factors fasting venous blood was drawn; c. psychological aspects: Eating Attitudes Test, Rosenberg self-esteem scale, Beck Depression Inventory, Eating Disorder Examination Questionnaire, Body Esteem Scale, Perceived Stress Scale were used.Results. The patient responded well to stimulation -apart from a mild headache. After tDCS sessions, improvement in anthropometric measurements, mood, and body self-esteem was observed. No severe changes in blood parameters were observed after the intervention.Conclusions. Described study case offer preliminary support for achieving meaningful clinical outcomes using transcranial stimulation. However, future clinical studies compared to the placebo group are necessary for proposing a new type of AN therapy.